Nitrogen-doped graphene-supported transition-metals carbide electrocatalysts for oxygen reduction reaction - Chen, Minghua (2015)
A novel and facile two-step strategy has been designed to prepare high performance bi-transition-metals (Fe- and Mo-) carbide supported on nitrogen-doped graphene (FeMo-NG) as electrocatalysts for oxygen reduction reactions (ORR). The as-synthesized FeMo carbide -NG catalysts exhibit excellent electrocatalytic activities for ORR in alkaline solution, with high onset potential (−0.09 V vs. saturated KCl Ag/AgCl), nearly four electron transfer number (nearly 4) and high kinetic-limiting current density (up to 3.5 mA cm−2 at −0.8 V vs. Ag/AgCl). Furthermore, FeMo carbide -NG composites show good cycle stability and much better toxicity tolerance durability than the commercial Pt/C catalyst, paving their application in high-performance fuel cell and lithium-air batteries.